Suggestions and Considerations for Application of Movement Screens to Clinical Practice - Andrew Skibski; James Onate; L. Colby Mangum (International Journal of Sports Physical Therapy)
Pre-participation and return to activity functional assessments are commonly used in clinical practice to assess movement quality and identify athletes' limitations. While there are slight differences between each specific test battery, general guidelines suggest that the tests be completed without a warm-up. This has been suggested because dynamic stretching may improve range of motion and athletic performance. However, athletes typically warm up prior to participating in sport. Therefore, researchers should investigate the acute effects of dynamic stretching on functional tests and movement screens and evaluate other factors that may influence performance on these test batteries. Scientific evidence for standardized implementation of various movement screens is lacking, and future research should aim to identify gaps in the literature to allow clinicians to properly implement evidence-based practice functional assessments. The purpose of this commentary is to discuss various considerations for implementing movement screens and assessment tools into clinical practice.